Investigation of the Electrical Properties of Transparent Conductive Oxides Thin Semiconductor Films Grown by Various Techniques - Al Mashary, Faisal (2019)
The main motivation of this thesis was to investigate the electrical properties of In-doped TiO2, Er-doped TiO2 and Er-doped In2O3 thin films. The effect of the growth techniques on the structural, electrical and optical properties of In-doped TiO2 thin films grown by pulsed laser deposition (PLD) and sputtering techniques were investigated. X-ray diffraction (XRD) and Raman revealed both rutile and anatase phases for the sputtered samples whereas only the anatase phase was observed for the PLD samples. Photoluminescence (PL) spectra unveiled several peaks which were explained by defect related optical transitions. The PLD samples were found to have better electrical properties and lower number of electrically active defects than those of the sputtered samples. The structural, optical and electrical properties of In-doped TiO2 grown on (100) and (311)B GaAs substrates by PLD were investigated. In doping was found to adversely affect the electrical properties of (100) samples, whereas it enhanced those of (311)B samples. XRD and PL measurements showed that samples grown on (311)B planes have better crystallographic properties when compared to samples grown on the conventional (100) plane. Two shallow defects were detected in all samples except for sample 15 (311)B where three shallow defects were observed. A red-shifted emission was also observed in sample 15 (311)B which was due to the presence of more shallow defects in this sample as compared to the other samples. As there is no significant difference in the electrical properties, it could be concluded that sample 15 (311)B is the best among all samples investigated in this work due to the red-shift that makes it more suitable for solar cell applications as compared to the other samples. Er-doped TiO2 thin films (Er:TiO2 TFs) have also been grown on p-type silicon substrates via a combination of an easy sol-gel process and spin coating technique. The obtained results provide strong evidence that Er doping improve the electrical properties and annihilates oxygen-related defects, especially for the highly doped samples. Hence, an enhancement in the sensitivity of UV detectors for Er doped samples is expected. In2O3 and Er doped In2O3 (Er:In2O3) thin films were grown on p-type Si (100) substrates by a spin-on technique. It was found that the less doped sample has the lowest leakage current density and better electrical properties while the undoped In2O3 sample has the highest leakage current density. It was also found that as the atomic fraction of Er increases, the reverse current density increases. The undoped In2O3 sample reveals four defects whereas only one defect could be detected in the less doped sample. The removal of oxygen related defects and the improvement of the electrical properties of the doped samples, especially for the less doped sample, would enhance the sensitivity of UV detectors for Er doped samples as compared to the undoped In2O3 samples.